K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

2 tháng 12 2015

\(x^2-3x-4=0\)

\(x^2+x-4x-4=0\)

\(x\left(x+1\right)-4\left(x+1\right)=0\)

\(\left(x-4\right)\left(x+1\right)=0\)

\(\Rightarrow x-4=0\) hoặc \(x+1=0\)

\(\Rightarrow x=4\) (loại) hoặc \(x=-1\) (thỏa mãn)

Vậy \(x=-1\)

29 tháng 2 2016

x2-3x-4=0

<=>x2-4x+x-4=0

<=>x(x-4)+(x-4)=0

<=>(x-4)(x+1)=0

<=>x-4=0 hoặc x+1=0

<=>x=4 hoặc x=-1

Vậy x\(\in\) {-1;4}

29 tháng 2 2016

x2-22-3x=0

=>(x-2)(x+2)-3x=0

=>(x-2)(x+2)-3x-6=-6

=>(x-2)(x+2)-(3x+6)=-6

=>(x+2)(x-2+3)=-6

=>(x+2)(x+1)=-6

Tiếp theo tự lập công trình ước số để làm

a: (2x-3)(3x+6)>0

=>(2x-3)(x+2)>0

=>x<-2 hoặc x>3/2

b: (3x+4)(2x-6)<0

=>(3x+4)(x-3)<0

=>-4/3<x<3

c: (3x+5)(2x+4)>4

\(\Leftrightarrow6x^2+12x+10x+20-4>0\)

\(\Leftrightarrow6x^2+22x+16>0\)

=>\(6x^2+6x+16x+16>0\)

=>(x+1)(3x+8)>0

=>x>-1 hoặc x<-8/3

f: (4x-8)(2x+5)<0

=>(x-2)(2x+5)<0

=>-5/2<x<2

h: (3x-7)(x+1)<=0

=>x+1>=0 và 3x-7<=0

=>-1<=x<=7/3

30 tháng 12 2015

(x-1)^2=4

=>(x-1)^2=2^2=(-2)^2

mà x<0

=>(x-1)^2=(-2)^2

=>x-1=-2

=>x=-2+1

=>x=-1

vậy x=-1

tick nhé

30 tháng 12 2015

(x-1)2=4

(x-1)2=22

x-1=2

x=2+1

x=3

29 tháng 9 2017

a) x =\(\dfrac{-3}{4}\)

30 tháng 9 2016

\(x\le\frac{1}{12}\) hoặc \(x\ge5\)

b,\(x\le\frac{1}{16}\)